PENGARUH TERAPI BEKAM TERHADAP PENURUNAN KELUHAN KESEHATAN PADA PASIEN DI YAYASAN ALJANNAH SUMATERA BARAT DI ERA SOCIETY 5.0 - Bhagas Yudhanto, Satrio; Al Ashari, Muhammad; Alfauzain, Alfauzain; Wisandra, Ade; Ilahi, Vitratul; Aulia, Mirza; Aini, Rafika (Ensiklopedia of Journal, 2025)
This study aims to analyze the effect of cupping therapy on the reduction of health complaints in patients at Yayasan Aljannah Sumatera Barat in the Society 5.0 era. The research used a qualitative method with in-depth interviews as the data collection technique, involving the foundation’s management and patients undergoing cupping therapy. The results showed that cupping therapy had a positive impact on reducing health complaints such as muscle pain, digestive disorders, and stress. Most patients reported significant improvements in sleep quality, feeling more energetic, and a reduction in anxiety levels after undergoing cupping therapy. The frequency of therapy also influenced the success rate, with patients who underwent therapy more regularly reporting better outcomes. However, some patients did not experience significant changes, particularly those with chronic health issues. The study also found that education and the use of technology to introduce cupping therapy to the public are essential to increase acceptance and access to this therapy. Overall, cupping therapy proved effective as an alternative treatment in reducing health complaints and can be a beneficial therapy option in the Society 5.0 era.Keywords: Standard Inpatient Class, Readiness, Implementation